Discovering the Prosodic Domain of Aceh Hakka Tone Sandhi - Lee, Johnny; Ling, Wang-Chen (Bina Nusantara University, 2022)
The research investigated the tonal system of the Hakka dialect spoken in the Aceh province of Indonesia. The aim of the research was twofold. First, it retranscribed the dialect’s tonal inventory and provided a comparison with Meixian Hakka and the inventory found in Chen’s (2007) research. Second, it analyzed the Shang Tone Sandhi Rule (STSR) of the dialect and its prosodic domain. The data were collected with a careful design based on the number of syllables, different prosodic structures, and a variety of tonal combinations. The data were collected from two informants, who were female Hakka native speakers that originated from Banda Aceh, Indonesia. The research used mainly an impressionistic approach with some support from Praat Version 6.2.14 to evaluate the pitch of the tones. As for the research’s transcription, the researchers opt for the simpler yet phonologically distinct three-level height system (H, M, L) rather than the five-pitch category of Chao. The research identifies that there are six tonal values in this dialect. The tonal alternation rule, i.e., STSR, operates in a multisyllabic domain, and only the tone at the end of a domain is intact from tonal alternation. The STSR is not sensitive to the syntactic domain c-command relation of the Direct Reference Hypothesis. It also behaves differently compared to the Guangxing dialect Yangping Tone Sandhi Rule. As for prosody, the hierarchical domain of the rule in Aceh Hakka is bounded within the Utterance (U), which is different from the Yinping tone sandhi domain in Meinong Hakka, in which tone sandhi is blocked by the I domain (intonational phrase domain). Therefore, the researchers postulate that the domain for Aceh Hakka Shang tone sandhi lies in the Utterance (U).